Infection rates associated with epidural indwelling catheters for seven days or longer: systematic review and meta-analysis - Ruppen, W; Derry, S; McQuay, H; Moore, R (BioMed Central, 2007)
Background: To determine infection rate with use of epidural catheters in place for seven days or more. Methods: Systematic review and pooled analysis of observational studies. Results: Twelve studies with 4,628 patients (median 197 patients) provided information, of which nine (4,334 patients) were published after 1990. Eight studies (3,893 patients) were retrospective, and four studies (735 patients) prospective. Electronic searches identified three studies and searching reference lists nine. There were 257 catheter-related infections in total, of which 211 were superficial and 57 deep, giving rates of 6.1%, 4.6% and 1.2% respectively. Ten of the 12 studies had deep infection rates of 2% or less. The incidence of deep infection was 1 per 2391 days of treatment, or 0.4 per 1000 catheter treatment days. In nine studies (1503 patients), predominantly in cancer, and with average catheter duration of 74 days, the deep infection rate was 2.8%. The proportion of patients with infection of any type was higher in cancer patients with longer catheter duration. Limited numbers of events meant that no reliable estimate of the impact of prospective and retrospective design could be made. There appeared to be a relationship between catheter duration and infection rate from this and other recent estimates. Four of 57 (7%) patients with deep infection died. Conclusion: The best estimate is that one person in 35 with an epidural catheter in place for 74 days for relief of cancer pain can be expected to have a deep epidural infection, and that about 1 in 500 may die of infection-related causes. This is a most uncertain estimate given the limited nature of the evidence.